Appearance of monoclonal plasma cell diseases in whole‐body magnetic resonance imaging and correlation with parameters of disease activity. Issue 10 (17th April 2014) - Kloth, Jost K.; Hillengass, Jens; Listl, Karin; Kilk, Kerstin; Hielscher, Thomas; Landgren, Ola; Delorme, Stefan; Goldschmidt, Hartmut; Kauczor, Hans‐Ulrich; Weber, Marc‐André
<x xml:space="preserve">Abstract</x> The aim of our study was to assess in which way different infiltration patterns of monoclonal plasma cell diseases in whole‐body (wb) magnetic resonance imaging (MRI) are associated with clinical stages, plasma cell content in bone marrow samples and established serum markers of disease activity. Institutional review board approval was obtained. We performed wb‐MRI in 547 consecutive, unselected and untreated patients with monoclonal gammopathy of undetermined significance (MGUS, n = 138), smoldering myeloma (SMM, n = 157) and multiple myeloma (MM, n = 252) on two 1.5 T MRI‐scanners with body array coils. The studies were evaluated in consensus by two experienced radiologists blinded to the diagnosis. We observed focal lesions in 23.9% (MGUS), 34.4% (SMM) and 81.3% (MM), respectively. A diffuse infiltration pattern was detected in 38.4%, 45.9% and 71%, respectively. The differences between all infiltration patterns were significant (p < 0.0001). The presence of focal lesions and the presence of a diffuse bone marrow infiltration was associated with an increased plasma cell percentage in bone marrow samples (median 22% vs. 14%, 26% vs. 10%, both p < 0.0001) and monoclonal protein concentration (median 18 g/dl vs. 13 g/dl, p = 0.003, 20 g/dl vs. 11 g/dl, p < 0.0001). Further categorization of the diffuse infiltration patterns in wb‐MRI into "salt‐and‐pepper, " moderate and severe identified significant associations with M‐protein (median g/dl for S+P/moderate/severe 23/18/25, p = 0.04), plasma cell percentage in the bone marrow (median 25%/24%/40%, p = 0.02), and age (median years 67/60/57, p < 0.0001). Bone marrow infiltration in wb‐MRI is significantly different between the various stages of plasma cell disease and correlates well with established markers of disease activity.